Ventilation systems : design and performance - Awbi, H. B. (Hazim B.), 1945- (London ; New York : Taylor & Francis, 2008)
A guide to ventilation systems. It presents the advanced developments in ventilation research and its applications. It also covers the fundamentals.
This comprehensive reference guide to ventilation systems provides up-to-date knowledge based on the experience of internationally-recognized experts to deal with current and future ventilation requirements in buildings. Presenting the most recent developments in ventilation research and its applications, this book covers the fundamentals as well as more advanced topics. With rigorous coverage for researchers and a practical edge for building professionals, Ventilation Systems is the one stop guide for the subject.
Airflow, heat and mass transfer in enclosures -- Ventilation and indoor environmental quality -- Energy implications of indoor environment control -- Modeling of ventilation airflow -- Air distribution : system design -- Characteristics of mechanical ventilation systems -- Characteristics of natural and hybrid ventilation systems -- Measurement and visualization of air movements.
Includes bibliographical references and index.
Keywords: Ventilation